A recyclable polyoxometalate-based supramolecular chemosensor for efficient detection of carbon dioxide. Issue 12 (29th September 2015) - Wei, Haibing; Zhang, Jinlong; Shi, Nan; Liu, Yang; Zhang, Ben; Zhang, Jie; Wan, Xinhua
Abstract : A new type of supramolecular chemosensor based on a polyoxometalate and a block copolymer was constructed for the qualitative and quantitative detection of CO2 . Abstract : A new type of supramolecular chemosensor based on the polyoxometalate (POM) Na9 DyW10 O36 (DyW10 ) and the block copolymer poly(ethylene oxide- b-N, N -dimethylaminoethyl methacrylate) (PEO114 - b -PDMAEMA16 ) is reported. By taking advantage of the CO2 sensitivity of PDMAEMA blocks to protonate the neutral tertiary amino groups, CO2 can induce the electrostatic coassembly of anionic DyW10 with protonated PDMAEMA blocks, and consequently trigger the luminescence chromism of DyW10 due to the change in the microenvironment of Dy 3+ . The hybrid complex in dilute aqueous solution is very sensitive to CO2 content and shows rapid responsiveness in luminescence. The luminescence intensity of the DyW10 /PEO- b -PDMAEMA complex increases linearly with an increasing amount of dissolved CO2, which permits the qualitative and quantitative detection of CO2 . The complex solution also shows good selectivity for CO2, with good interference tolerance of CO, N2, HCl, H2 O and SO2 . The supramolecular chemosensor can be recycled through disassembly of the hybrid complex by simply purging with inert gases to remove CO2 .